Paradigma pendidikan demokratis : sebuah model pelibatan masyarakat dalam penyelenggaraan pendidikan - Rosyada, Dede, 1958- (Jakarta : Prenada Media, 2004)
On democratization of education and community participation related to educational reform in Indonesia.
Includes bibliographical references (pages [313]-320) and index.
Keywords: Democracy and education -- Indonesia; Community education -- Indonesia; Educational change -- Indonesia; Education -- Indonesia